2019
DOI: 10.1177/0886260519888186
|View full text |Cite
|
Sign up to set email alerts
|

Behind Closed Doors: The Role of Risky Lifestyles and Victimization Experiences on Fear of Future Victimization Among South Korean Inmates

Abstract: Criminologists have long considered the extent to which victimization experiences influence fear of future victimization. As a result, some scholars have proposed risky lifestyles theory as a theoretical framework linking individuals’ lifestyles and experiences to their fear of victimization. This study contributes to and extends this line of research by exploring whether risky lifestyles and prior victimization influence fear of future victimization among a large sample of incarcerated felons in South Korea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 97 publications
(151 reference statements)
0
12
0
Order By: Relevance
“…A large body of survey-based work has shown that perceptions of procedural justice are directly and indirectly associated with greater compliance with the law and rules, e.g., [28][29][30]. Moreover, risky lifestyles within the incarceration setting are often illegal activities (e.g., participation in gambling) [31,32]. Accordingly, the argument we advance in this article is two-prong.…”
Section: Literature Reviewmentioning
confidence: 92%
See 2 more Smart Citations
“…A large body of survey-based work has shown that perceptions of procedural justice are directly and indirectly associated with greater compliance with the law and rules, e.g., [28][29][30]. Moreover, risky lifestyles within the incarceration setting are often illegal activities (e.g., participation in gambling) [31,32]. Accordingly, the argument we advance in this article is two-prong.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Details regarding the rationale and overall design of the study can be found in Yoon [70]. The data we drew on in this article have been used in several empirical studies [31,65,[71][72][73][74], but have not been used to test how risky lifestyles mediate the association between procedural justice and violent misconduct. Table 1 shows the descriptive information of participants.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Fear of crime, including its many dimensions (see , may also be placed within the L-RAT framework (e.g., Choi & Dulisse, 2019;. However, the way in which various activities may help explain differences in fear of crime can be interpreted quite differently (see e.g., ).…”
Section: Lifestyle-exposure Theory and Routine Activity Theorymentioning
confidence: 99%
“…The importance of everyday life is emphasized in lifestyle-exposure theory and routine activity theory, as these theories state that victimization is a result of exposure to environmental circumstances favorable to victimization . Although less common, research based on these theories also has examined whether activities from daily life are related to fear of crime (see e.g., Choi & Dulisse, 2019;.…”
Section: Introductionmentioning
confidence: 99%